The Titanic Remembered 1912-2012 - Beau Riffenburgh (Wildebest Publishing Ltd, 2011)
A century after it sank beneath the icy waves in the worst maritime disaster in seafaring history, the Titanic returns! The inclusion of some 40 facsimile items--blueprints and construction plans, telegrams from that fateful night, even a US Navy ice warning--makes this centennial edition a veritable treasure trove of historical memorabilia and hands-on historical detail. The included DVD offers firsthand accounts from survivors, rare film footage, original blueprints, safety reports, and more.